Endocannabinoids in Bladder Sensory Mechanisms in Health and Diseases - Stewart Christie; Simon Brookes; Vladimir Zagorodnyuk (Frontiers Media S.A., 2021)
The recent surge in research on cannabinoids may have been fueled by changes in legislation in several jurisdictions, and by approval for the use of cannabinoids for treatment of some chronic diseases. Endocannabinoids act largely, but not exclusively on cannabinoid receptors 1 and 2 (CBR1 and CBR2) which are expressed in the bladder mainly by the urothelium and the axons and endings of motor and sensory neurons. A growing body of evidence suggests that endocannabinoid system constitutively downregulates sensory bladder function during urine storage and micturition, under normal physiological conditions. Similarly, exogenous cannabinoid agonists have potent modulatory effects, as do inhibitors of endocannabinoid inactivation. Results suggest a high potential of cannabinoids to therapeutically ameliorate lower urinary tract symptoms in overactive bladder and painful bladder syndromes. At least part of this may be mediated via effects on sensory nerves, although actions on efferent nerves complicate interpretation. The sensory innervation of bladder is complex with at least eight classes identified. There is a large gap in our knowledge of the effects of endocannabinoids and synthetic agonists on different classes of bladder sensory neurons. Future studies are needed to reveal the action of selective cannabinoid receptor 2 agonists and/or peripherally restricted synthetic cannabinoid receptor 1 agonists on bladder sensory neurons in animal models of bladder diseases. There is significant potential for these novel therapeutics which are devoid of central nervous system psychotropic actions, and which may avoid many of the side effects of current treatments for overactive bladder and painful bladder syndromes.